Business Process Evaluation of ITS Medical Center using Value Stream Mapping - Reisa Permatasari; Abdul Rezha Efrat Najaf; Bonda Sisephaputra (Future Science, 2022)
Patients at ITS Medical Center are the main subject of the healthcare business process. they tend to expect satisfactory service especially when ITS Medical Center serves as a first-rate health facility for BPJS. At the time of this research pre-conducted, their business process has not been visually described in the Business Activity Monitoring (BAM), which makes management cannot foresee the efficient business process. Previous research on the implementation of Value Stream Mapping (VSM) in the Emergency Department shows the possibility to apply VSM in a clinic. Therefore, we decided to evaluate the existing business processes by gathering information from the Event Log Review and conducting employee interviews. To propose future business processes, we followed the Lean Manufacturing practice from Toyota always looks at product value from the customer's point of view. The evaluation consists of Business Process Model and Notation (BPMN) between four actors; doctor, patients, medical records department, and pharmacy. Continued picturing it using VSM using criteria of ineffectiveness from Lean Manufacturing. ITS Medical Center's current VSM shows three areas of opportunities for improvement consisting of Movement, Transportation, and Extra Process. Whereas its future VSM finding results from the comparison of the current with the future business process, predicted that service time can be faster by a ratio of 8%, non-value-added time is reduced by 15%, and at the end of the day, average inefficiency is reduced by 27.54%. With more than quarterly efficiency can be decision support for new business model improvement and implementation.